2016
DOI: 10.3892/etm.2016.3085
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-101 has a suppressive role in osteosarcoma cells through the targeting of c-FOS

Abstract: MicroRNAs (miRs) have been implicated in the development and progression of osteosarcoma (OS). However, the underlying mechanism of miR-101 in regulating of the proliferation, migration and invasion of OS cells remains to be elucidated. In the present study, reverse transcription-quantitative polymerase chain reaction data revealed that miR-101 was frequently downregulated in the tissue samples of 12 patients with OS compared with their matched adjacent non-tumor tissues. Furthermore, miR-101 was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…As miRNAs usually exert their control by targeting downstream genes, the identification of miR-101 downstream target genes played an important role in understanding its potential mechanism. Previous studies have reported that miR-101 targets COX2, c-FOS, CXCR7, SOX9, EZH2 and Rac1 [11-14, 18, 19, 38]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As miRNAs usually exert their control by targeting downstream genes, the identification of miR-101 downstream target genes played an important role in understanding its potential mechanism. Previous studies have reported that miR-101 targets COX2, c-FOS, CXCR7, SOX9, EZH2 and Rac1 [11-14, 18, 19, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that miR-101 plays key roles in BC progression. Although miR-101 has been reported to target many downstream genes, including CDK8 [10], c-FOS [11], CXCR7 [18], SOX9 [14, 19] and GSK3β [20], the potential correlation between miR-101 and Sex-determining region Y-box 2 (SOX2) in BC is still unknown and needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike siRNAs, miRNAs have multiple target genes (15). As endogenous RNA interference is triggered, miRNAs regulate cells which are closer to a physiological level instead of regulation through a simple gene knockout (16). We found that downregulation of microRNA-95-3p expression suppresses cell growth, induced apoptosis, increased caspase-3 and caspase-9 activities and bax protein expression in osteosarcoma cells; overexpression of microRNA-95-3p increased cell growth, and inhibited apoptosis of osteosarcoma cells, suggesting that microRNA-95-3p has a potential benefit in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, growing evidences have indicated that miRNAs could be employed as novel bio-markers for non-invasive detection of various diseases, especially tumors [7,8]. Among these miRNAs, miR-101 is identi ed as a tumor suppressor, and its abnormal expression was observed in a variety types of human tumor, such as heaptatocellular carcinoma, osteosarcoma, etc [9,10]. It was reported that miR-101 could inhibit tumor cell proliferation and invasive capacity, thus played an inhibitory role in development of cancer [11,12].…”
Section: Introductionmentioning
confidence: 99%